ЛЕГЕНДЫ О ПОЛКОВНИКЕ ГАРАНИНЕ В ТЕКСТАХ ВОСПОМИНАНИЙ КОЛЫМСКИХ ЗАКЛЮЧЁННЫХ - Горбачевский, Чеслав (Acta Neophilologica, 2014)
This article is devoted to the Kolyma legend formed during Stalin’s regime. The legend was spread amongst the convicts of Kolyma after Garanin’s arrest at the end of 1938. Garanin was known as a chief of the USVITL (Dalstroj) from 1937 to 1938. A great number of Kolyma’s convicts focused in their own memoirs on eternal problems, connecting ordinary events with totalitarian times: Garanin was an omnipotent chief for more than a year. After a short period of time he lost all his power and influence (he was arrested and died in prison).